KREATIVITAS BELAJAR, TINGKAT PENDIDIKAN ORANG TUA, DAN PENDAPATAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA SMK AL-HUDA JATIMULYO KABUPATEN LAMPUNG SELATAN - Afif Rahman Riyanda (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2020)
This research aim to to know Influence of creativity learn, storey;level education of old fellow to motivation learn student SMK Al-Huda of regional South Lampung. Method the used descriptive and asosiatif with quantitative approach, with amount of population counted 75 and people of sampel 75 people. Technique intake of sampel totally Sampling, motivation learn student, creativity learn, storey;level education of old fellow and earnings of old fellow obtained from result of spreading of kuesioner. Analysis which used in this research descriptive analysis and inductive analysis consisting of classic assumption test, doubled linear regression analysis and hypothesis test. Result of this research indicate that ( 1) creativity learn to have an effect on positive and signifikan to motivation learn ( 2)Eeducation of Old Fellow have an effect on positive and signifikan to motivation learn ( 3)Earnings old fellow have an effect on positive and signifikan to motivation learn, and ( 4) Creativity learn, Storey;Level Education of Old fellow and Earnings of Old Fellow have an effect on positive and signifikan to motivationlearn.